The Effect Of Adding Celery Leaves On The Quality Of Snow White Cookies - Pratama, Muhammad Reihan; Faridah, Anni; Elida, Elida; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Snow princess cookies are one of the pastries that are very popular with Indonesian people, however, the variety of snow princess cookies is currently still lacking. Currently, the use of celery is still limited as a processed vegetable, so there is a need for innovation in processed celery. It is hoped that the addition of celery leaves can provide innovation in Snow White cookies because it provides a natural green color and also increases the fiber content and nutritional value of Snow White cookies. The aim of the research was to analyze the effect of adding celery leaves on the quality of Snow White cookies in terms of shape, color, aroma, texture and taste, this was motivated by the lack of variety in Snow White cookies. The use of celery is still not widely known by the public, the use of celery is only limited to processed vegetables. This type of research is pure experiment (true experiment). The research design used was a completely randomized design (CRD). Data was obtained from 3 limited panelists, using an organoleptic test format, then the data was analyzed using the analysis of variance test (ANOVA). If Fcount is greater than Ftable, then Duncan's test can be carried out. The research results show a significant influence on color quality. Meanwhile, the shape, aroma, texture and taste did not have a significant influence on the use of celery leaves on the quality of Snow White cookies. This is known from the conclusion which shows that the best overall score is neatly 3.78 (X0). The uniform shape was 3.78 in treatments (X1), (X2), (X3). Color 3.78 (X3) with green spots, aroma 4.00 (X0) fragrant category, texture 3.44 (X0) and (X3) not easily broken, texture 3.89 (X0) fragile, taste 4.00 (X0) sweet category.